(untitled) - Smith, George David (Cambridge, 1988)
Over the past century, Alcoa has developed from a small entrepreneurial venture to a giant corporation; from a one-dimensional, owner-managed firm to a complex managerial bureaucracy; from a domestic company to a multinational enterprise. In the process, Alcoa survived a difficult transition from its long-held position as a monopolist (of aluminum production) to its current status as a firm operating in highly competitive international markets. This book presents Alcoa's history, from its beginnings as a speculative venture seeking to exploit an untested technology, through its rise to become the most successful monopoly in American history. By World War II, no other American corporation had developed its industry's markets more dramatically and then dominated them more completely. The book analyzes the undoing of Alcoa's monopoly by war and antitrust, as well as how Alcoa adapted to evolving forms of competition.
Keywords: Aluminum company of america,Aluminum industry and trade; History,History; United states